From the hallways to the screens: Digitalization in the Argentine criminal justice system following covid-19 - Lio, Vanesa (2026)
During the covid-19 pandemic, digital technologies acquired a prominent role in Argentina. In the area of criminal justice, this was reflected in the accelerated transition towards a system of electronic processing of files, which allowed for the automatization of some procedures, the beginning of paperless processes, and the remote management of cases. Situated at the intersection of criminal justice sociology and science and technology studies, this article analyzes changes resulting from the incorporation of new technologies in the registry and processing of criminal cases. This analysis focuses on the reconfiguration of tasks that was necessary for guaranteeing access to justice in such an exceptional context, as well as changes that established new modes of action that have extended beyond the public health emergency. Through an empirical case study, based on documentary analysis and interviews, the article describes legal practices with the objective of identifying advances and obstacles that emerged from the encounter of criminal justice and technology in an unprecedented scenario. In conclusion, it is observed that this integration has not necessarily led to greater democratization nor to better access to the justice system.